Strategic Implementation of Planning in Information Systems and Information Technology in "XYZ High University" - Franklin Kharisma GENTA; Sugiyanto SUGIYANTO; Gijanto Purbo SUSENO; Adri ARISENA (International Journal of Environmental, Sustainability, and Social Science, 2021)
Information Technology Strategic Planning is a derivative of an institution's Strategic Plan (Renstra). The purpose of this research is to find the need for Information Systems and Information Technology (IS / IT) for institutions with a case study method of the Strategic Plan "XYZ College" The research begins with an analysis of the â€œPT XYZâ€ external and internal business environment to determine the five forces model and critical success factors. Next is an analysis of the external and internal IS / IT environment in order to determine world technology trends and the current application portfolio of institutions. The next stage is the strategic process (IS, IT, and IS / IT management. The final stage is to determine the institute's future IS / IT applications. The results achieved are recommendations for the IS / IT application portfolio that "PT XYZ" should have.